2005
DOI: 10.1002/jmri.20405
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced MRI of ductal carcinoma in situ: Characteristics of a new intensity‐modulated parametric mapping technique correlated with histopathologic findings

Abstract: Purpose:To identify morphologic and dynamic enhancement magnetic resonance imaging (MRI) features of pure ductal carcinoma in situ (DCIS) by using a new intensitymodulated parametric mapping technique, and to correlate the MRI features with histopathologic findings. Materials and Methods:Fourteen patients with pure DCIS on pathology underwent conventional mammography and contrast-enhanced (CE) MRI using the intensity-modulated parametric mapping technique. The MR images were reviewed and the lesions were categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Nevertheless, a late subtraction series should be routinely evaluated in the normal clinical setting as there are a few invasive lobular carcinomas that enhance slowly, additionally to premalignant or benign lesions, that could be of clinical relevance. Mariano et al showed that only 50% of the DCIS lesions enhance with type 2 or type 3 curves in the time signal intensity curve [32]. The late subtraction series may also be helpful to estimate the size of a malignant lesion as an eventually surrounding DCIS may be better identified in the late phase of the dynamic scan.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, a late subtraction series should be routinely evaluated in the normal clinical setting as there are a few invasive lobular carcinomas that enhance slowly, additionally to premalignant or benign lesions, that could be of clinical relevance. Mariano et al showed that only 50% of the DCIS lesions enhance with type 2 or type 3 curves in the time signal intensity curve [32]. The late subtraction series may also be helpful to estimate the size of a malignant lesion as an eventually surrounding DCIS may be better identified in the late phase of the dynamic scan.…”
Section: Discussionmentioning
confidence: 98%
“…They recommend either direct MR-guided vaccum-assisted biopsy or short-term follow-up breast MRI within 3 months 15 . Libermann et al found that the PPV of biopsy for lesions identifi ed in breast MRI signifi cantly increased with increasing size of the lesion and biopsy is rarely necessary for lesions smaller than 5 mm because of their low likelihood of cancer 19 . If the diagnostic centre for breast is interested in MRI examination seriously, it should be well equipped for doing biopsy and localization under MRI control.…”
Section: Discussionmentioning
confidence: 99%
“…Each high-resolution 3DSSMT pixel hue was modulated as a function of the corresponding k21 at the same location according to a color scheme ranging from blue (k21 = 0.00/sec-ond) to blue-green (k21 = 0.005/second), green (k21 = 0.01/second), green-yellow (k21 = 0.015/sec-ond), and yellow (k21> 0.02/second) (19). Using the parametric mapping technique, lesions were classified as suspicious if parametric maps revealed a green-yellow or yellow color, or if the k21 value was ≥ 0.015/second (6,7). A score for the overall likelihood of cancer was assessed for each lesion based on the combined lesion morphology, contrast dynamics, and k21 parametric mapping on MRI and rated using the ACR Breast Imaging and Reporting Data System (BIRADS) final assessments of 1–5, with 5 representing the highest suspicion of malignancy (18).…”
Section: Methodsmentioning
confidence: 99%
“…(14,15). However, results of previous studies also demonstrated that the choline levels may not be as greatly elevated in some breast cancers as they are in others, and sometimes are not detected at all, resulting in false-negative diagnoses (7,13,15). …”
mentioning
confidence: 94%
See 1 more Smart Citation